Preeclampsia: A Complicated Pregnancy Condition-An Overview, Diagnosis, Management, and Nursing Interventions - Saad, Fatimah Mohammed; Al Rutaiq, Abdulrahman Hamad; Mohammed, Aisha Ali Y; Saad, Samirah Mahammad; Aljohani, Ayesha Ayedh Hamdan; Alyousef, Abdullah Hamad; Baksh, Asma Yousef Khada; Alablan, Mona Hassan; ALMOTAIRI, AFRAH NAIF MARZOQ; Abuamria, Reem Nasser Hassan (Journal of Ecohumanism, 2024)
Background: Preeclampsia is a hypertensive disorder in pregnancy that affects 2–8% of pregnancies globally, contributing significantly to maternal and neonatal morbidity and mortality. It typically arises after 20 weeks of gestation, with varying severity and associated complications such as eclampsia and HELLP syndrome. Despite advances in diagnosis and management, its etiology remains incompletely understood. Aim: This article provides an overview of preeclampsia, focusing on its pathophysiology, epidemiology, clinical diagnosis, management strategies, and nursing interventions. Methods: A comprehensive review of the literature was conducted to outline diagnostic criteria, clinical features, and management strategies for preeclampsia. Key interventions, including antihypertensive therapy and seizure prophylaxis, were detailed alongside evidence-based nursing practices. Results: Preeclampsia manifests in two subtypes—early-onset and late-onset—with differing pathophysiological mechanisms. Diagnostic criteria include sustained hypertension, proteinuria, and organ dysfunction. Effective management involves timely diagnosis, blood pressure control using agents like labetalol and nifedipine, and seizure prophylaxis with magnesium sulfate. Nursing care focuses on monitoring maternal-fetal health, educating patients, and providing emotional support. Conclusion: Early detection and timely intervention are critical in managing preeclampsia to prevent severe complications. A multidisciplinary approach, incorporating medical and nursing care, is essential to improve maternal and neonatal outcomes. Further research is required to elucidate the disease’s pathogenesis and optimize treatment strategies.